THE EFFECT OF HANDGRIP TRAINING AND RACKET MODIFICATION TRAINING ON SHORT SERVICE ABILITY IN BADMINTON GAMES ON PANRITA CLUB AND SAMUDRA CLUB ATHLETES - Jayadi, Jayadi; Dos Santos, Maria Herlinda; Rijaluddin, Khalid; Ilahi, Rahmat; Hardi, Alif Aryadi (Riyadhoh : Jurnal Pendidikan Olahraga, 2024)
Badminton is one of the popular sports and is loved by many people. Badminton also consists of several techniques including racket grip, hitting technique, standing posture, and position and footwork. Therefore, physiotherapy techniques are needed to improve and maximize the grip strength of badminton players which is commonly called Handgrip. This study aims to determine the effect of handgrip training and racket modification training on short serves. The type of research used is quantitative research with experimental research methods. The sample in this study amounted to 30 people who were divided into two groups with each group consisting of 15 people. The research sample was selected using the Random Sampling technique. The data analysis technique used is the dependent t-test analysis technique. The results obtained in this study with a p-value of 0.109 > 0.05 which shows that there is no significant difference between handgrip training and racket modification on short serve ability but handgrip training is more effective than racket modification training with handgrip training, namely mean difference 9.067 and p-value 0.000 < 0.005 while racket modification training means difference 5.867 and p-value 0.000 < 0.005.This shows that both exercises are equally good for improving short serve skills in badminton. Thus, it is hoped that athletes can improve their short serve skills in badminton by routinely performing physiotherapy movements such as handgrip or other exercises such as racket modification exercises.